Mending the broken valentine heart: a case report. Issue 8 (5th August 2022) - Marwaha, Sarandeep; Bhatia, Raghav; Papadakis, Michael; Marciniak, Anna
Abstract: Background: Mortality from myocardial infarction (MI) has been decreasing since the introduction of primary percutaneous intervention. Late complications still pose a dilemma, such as deterioration of left ventricle (LV) function, LV aneurysms, and LV thrombus formation. If not adequately managed in a timely manner, this can result in life-threatening consequences. Restoration of LV function by surgical resection of the infarcted LV wall is an option for a few complicated cases, with variable outcomes. Case summary: A 66-year-old man presented with dyspnoea 2 years after his initial MI, which was treated with a drug-eluting stent to his left circumflex artery. His Warfarin had been stopped after 6 months of treatment of a small LV thrombus, which was noted at the time of his initial infarction. His echocardiogram on admission demonstrated severe LV systolic impairment of 23% (which had deteriorated from 40%) with a giant true aneurysm of the basal to mid-lateral wall, which resembled a Valentine heart. The presence of a large, organized thrombus filling the aneurysm complicated the case further. The patient underwent a resection of the LV aneurysm and thrombus. He remained asymptomatic and maintained a significant improvement of his LV function to 47% at his 5 months scan. Discussion: The importance of imaging post-large MI and follow-up imaging once thrombus resolution has occurred is crucial. Patients with large LV aneurysm associated with severe refractory LV impairment and LV thrombus should be considered for LV aneurysmectomy for prognostic benefit and symptom relief.